Promoting access to higher education in an unequal society - Walton, Elizabeth; Bowman, Brett; Osman, Ruksana (South African Journal of Higher Education, 2016)
This short paper serves as an introduction to the collection of papers in this special issue of The South African Journal of Higher Education. First, the editors set the scene by commenting on access and throughtput in South African higher education, showing how these continue to be racially skewed, and linked to an inequitable education system. It is then observed that some of the intervention programmes that are offered at tertiary level do not always achieve their intended goals, and that interventions are increasingly being sought at secondary school level. Second, the editors introduce and briefly comment on the seven papers selected for this special issue, noting the particular contribution each makes to an understanding of the theme of promoting access to higher education in an unequal society. Third and in conclusion, the editors point to three issues that they believe emerge from the papers, and which are argued to be important in mapping the way forward. These are: the need to acknowledge that injections of finance may secure access, but do not necessarily secure success; a concern about the proliferation and fragmentation of interventions which do not ultimately have systemic impact; and the need for multi-site, multi-method and longitudinal studies that track the experiences of students through university and beyond.